Survey of the Existence of Tuberculosis Risk Factors and Their Reasons in Sufferers in Medan City - Afra Nabila Ansar; Mateus Sakundarno Adi; Henry Setyawan; Ari Udijono (Universitas Pahlawan Tuanku Tambusai, 2025)
The still high number of tuberculosis cases in Medan City is proof that the value of health is still low. This is proven by the high number of tuberculosis cases at the Sentosa Baru Community Health Center. Therefore, it is necessary to know the existence of risk factors for tuberculosis and the reasons for them in sufferers in the Sentosa Baru Community Health Center working area. This type of research is descriptive observational research with a cross-sectional approach. The sample in this study was 64 respondents who were tuberculosis sufferers in the work area of the Sentosa Baru Health Center. The research results show that the majority are of productive age with a high school education level and good (50%) or less (50%) knowledge. Smoking habits were primarily found in the moderate category (31.3%), and the habit of wearing masks was minimal (65.5%). Most had the habit of opening windows (67.2%) but had never removed phlegm in a particular container (40.6%). Observation results showed that the majority already had floors (87.5%) and walls (78.1%) that met the requirements, but only (15.6%) had glass tiles in their homes. Based on the results of cross-tab research, a comparison was made between the level of knowledge, age, level of education, and risk factors. It was concluded that age, level of education, level of knowledge, type of floor, type of wall, availability of glass tiles, smoking habits, habits of wearing masks, habits of opening windows, and habits of expelling phlegm were the reasons that influenced this.